Parenting Styles and Coping Strategies among Vietnamese Adolescents - Huong, Tran Thu; Huong, Tran Thu; Ha, Pham Manh; Dung, Pham Hanh; Tram, Trinh Bao; Thoa, Nguyen Thi Kim (Journal of Ecohumanism, 2024)
Coping ability is one of the crucial factors helping adolescents face and overcome changes and difficulties during this developmental stage. The selection and use of coping strategies by adolescents are influenced by various factors from family, school, and social environment, including parenting styles. This study aims to examine the influence of parenting styles, as perceived by adolescents, on their coping strategies. Using a cross-sectional design, the study employed the Proactive Coping Inventory and Parenting Scale. Results showed that parental autonomy support, psychological control, and behavioral control have different effects on adolescents' coping strategies.